Causes and Predictors of 30-Day Readmission After Shoulder and Knee Arthroscopy: An Analysis of 15,167 Cases. - Westermann, Robert W; Pugely, Andrew J; Ries, Zachary; Amendola, Annunziato; Martin, Christopher T; Gao, Yubo; Wolf, Brian R (Arthroscopy: The Journal of Arthroscopy & Related Surgery, 2015)
Purpose: To evaluate the incidence, causes, and risk factors for unplanned 30-day readmission after shoulder and knee arthroscopy.Methods: A multicenter, prospective clinic registry, the American College of Surgeons National Surgical Quality Improvement Program, was queried for Current Procedural Terminology codes representing the most common shoulder and knee arthroscopic procedures. Unplanned readmissions within 30 days were evaluated dichotomously, and causes of readmission were identified. Univariate and multivariate logistic regression analyses were used to identify variables predictive of readmission.Results: In total, we identified 15,167 patients who underwent shoulder and knee arthroscopic procedures in 2012. Overall, 136 (0.90%) were readmitted within 30 days, and the rates were similar after shoulder (0.86%) and knee (0.92%) procedures. Readmissions were most common after arthroscopic debridement of the knee (1.56%) and lowest after rotator cuff and labral repairs (0.68%) and cruciate reconstructions (0.78%). The most common causes of readmission were surgical-site infections (37.1%), deep venous thrombosis and pulmonary embolism (17.1%), and postoperative pain (7.1%). Multivariate analysis identified age older than 80 years (odds ratio [OR], 3.5; 95% confidence interval [CI], 1.5 to 8.1), chronic steroid use (OR, 3.3; 95% CI, 1.5 to 7.2), and elevated American Society of Anesthesiologists class (OR, 4.2; 95% CI, 1.4 to 12.0) as independent risk factors for readmission.Conclusions: The rate of unplanned readmissions within 30 days of shoulder and knee arthroscopic procedures is low, at 0.92%, with wound-related complications being the most common cause. In patients with advanced age, with chronic steroid use, and with chronic systemic disease, the risk of readmission may be higher. These findings may aid in the informed-consent process, patient optimization, and the quality-reporting risk-adjustment process.Level Of Evidence: Level III, prognostic study.